Emerging adults’ neuroticism links with depressive symptoms through personal belief in a just world and forgiveness - Quan, Sixiang; Kang, Huibin; Yang, Xiaohui (Frontiers in Psychology, 2025)
High neuroticism is a stable risk predictor of depressive symptoms. Researchers struggled to understand how neuroticism linked with depressive symptoms. The aim of the current study was to explore whether personal belief in a just world and forgiveness acted as mediators in the relations between neuroticism and depressive symptoms among emerging adults. A total of 630 non-clinical undergraduates completed questionnaires about the studied variables. A sequential mediation model with personal belief in a just world and forgiveness as mediators of the association between neuroticism and depressive symptoms was explored. The results found both direct and indirect effects of neuroticism on depressive symptoms. The sequential mediation analyses revealed that the positive relationship between neuroticism and depressive symptoms was simply and sequentially mediated by personal belief in a just world and forgiveness. These results suggested that neuroticism increased the risk of depressive symptoms by reducing the personal belief in a just world and forgiveness, as well as by the sequential mediating effects of personal belief in a just world and forgiveness. The implementing interventions specifically focused on elevating the level of personal belief in a just world and forgiveness may be important for ameliorating the depressive symptoms.